ABDURRAHMAN WAHID’S CONCEPT OF NON-VIOLENT APPROACH TO BUILDING PEACE - Muhammad Saiful Mujab (Teosofia: Indonesian Journal of Islamic Mysticism, 2015)
Abdurrahman Wahid is a prominent moslem scholar in Indonesia and Indonesia’s fourth president (and the first president voted by people’s representative council). He was born from traditionalist muslim family. His grand father is Hasyim Asy’ary, the founder of Nahdlatul Ulama’, the biggest islamic organization in theworld with 25 million member. His father, Wahid Hasyim, is the first minister of religious affairs. He was also the chairman of Nahdlatul Ulama’ for several periods.His contribution to create peace is countless. He is well known as the father of pluralism in Indonesia. After his death, many people started to fund organizations learning about his thoughts of pluralism, culture and religion, protecting minorities, respecting diversities, creating peace, etc.This article is attempting to explain his non-violance approach to create peace, in the case of terrorism prefention. Firstly, the writer define the term terrorism in general and Abdurrahman Wahid’s version. Secondly, it is explained three backgrounds of the emergence of terrorism; (1). the feeling of inferiority (2). Superficial understanding towards religion (3) the weak system of Indonesia government. And the third is the solution of those three causes; (1). Dialogue (2). Islamic Education (3). Improving the system of the government.